Heterologous Expression of the Class IIa Bacteriocins, Plantaricin 423 and Mundticin ST4SA, in Escherichia coli Using Green Fluorescent Protein as a Fusion Partner - Vermeulen, Ross Rayne; Van Staden, Anton Du Preez; Dicks, Leon (Frontiers in Microbiology, 2020)
The antilisterial subclass IIa bacteriocins, plantaricin 423 and mundticin ST4SA, have previously been purified from the cell-free supernatants of Lactobacillus plantarum 423 and Enterococcus mundtii ST4SA, respectively. Here we present the fusions of mature plantaricin 423 and mundticin ST4SA to His-tagged green fluorescent protein (GFP) for respective heterologous expression in Escherichia coli. Fusion of plantaricin 423 and mundticin ST4SA to His-tagged GFP produced the fusion proteins GFP-PlaX and GFP-MunX, respectively. Both fusion proteins were autofluorescent, circumvented inclusion body formation and lowered the toxicity of subclass IIa bacteriocins during heterologous expression. Not only did GFP-class IIa fusion stabilize heterologous expression and boost yields, the fluorescent intensity of GFP-PlaX and GFP-MunX could be monitored quantitatively and qualitatively throughout expression and purification. This robust fluorometric property allowed rapid optimization of conditions for expression and bacteriocin liberation from GFP via the incorporated WELQut protease cleavage sequence. Incubation temperature and IPTG concentration had a significant effect on bacteriocin yield, and was optimal at 18℃ and 0.1-0.2 mM, respectively. GFP-MunX was approximately produced at a yield of 153.30 mg/L culture which resulted in 12.4 mg/L active mundticin ST4SA after liberation and HPLC purification. While GFP-PlaX was produced at a yield of 121.29 mg/L culture, evidence suggests heterologous expression resulted in conformation isomers of WELQut liberated plantaricin 423.